ON THE ORGANIZATIONAL AND LEGAL BASIS OF INDUSTRIAL PARKS - Biriukov, Pavel Nikolaevich (SCIENTIFIC BULLETIN OF POLISSIA, 2017)
Urgencyoftheresearch. Current world is actively developing IP industrial parks (hereinafter IP). In foreign legal science main types of existing IP’s, are carefully study the themes of organizational and legal framework for the existence of IP.Target setting. Meanwhile, IP’s infrequently became the subject of research in Russian science. Researches are “scrappy”, and affect local aspects of this problem.Actual scientific researches and issues analysis. Domestic science has no clear picture of IP’s legal regulation at the Federal and regional levels,as well as it is “not in touch” withcontemporary problems ofIP’sfunctioning.Uninvestigatedparts of general matters defining. Domestic science has no clear picture of IP’s legal regulation at the Federal and regional levels, contemporary problems of functioning of IP.The research objective. Under such circumstances, it is necessary to identifythe prerequisites for the creation of IP in a territory characterized by the basic scheme of formation of IP’s in the region and their relationship with direct invest-ments. Among the objectives of the analysis of the legal regu-lation of IP algorithm of their formation and interaction of re-gional authorities and IP residents.The statement of basic materials.The article identifies preconditions for the formation of the IP. Among them: a substantial degree of activity of the authorities, the high level of innovation and considerable human resources. Preference turns high-tech industries, energy saving technologies, using environmentally friendly processes. Also enjoy priority in production, which hasa high level of added value and the most efficient processing. For example, the Voronezh Oblastexamines legal rules governing the formation and operation of PIS. Explores the advantages of placing companies in the IP’s territory. Great attention is paid to the essential conditions of the contracts, concludedfor the exercisesof investment activities. Explores the mechanisms of State support for companies using this instituteon the borderline between economy and law. Characterized by legal grounds for termination of State support for resident companies.Conclusions. As a result of previously mentioned bene-fits of IP’s creation and manufacturing in the sphere of indus-trial production, led in the nclusion of the text to the eco-nomic nature of IP’s